Transcending constraints: female bodily discipline and resistance in Han Kang’s The Vegetarian - Nie, Zhixing; Kaur, Hardev (International Islamic University Malaysia, 2025)
Han Kang’s The Vegetarian (2015/2007) has been the subject of numerous scholarly explorations. Nevertheless, few studies have applied Michel Foucault’s theory of the body to examine the protagonist Yeong-hye’s struggle against societal norms. This paper fills this gap by analyzing how Yeong-hye’s body is disciplined, constrained, and reimagined within the frameworks of patriarchy and biopolitics. Through Foucault’s concept of the body as a site of power, we argue that Yeong-hye’s refusal to conform to societal expectations, such as her rejection of meat consumption and her attempts to “become a plant,” represents both a personal rebellion and a tragic reflection of the limitations imposed by patriarchal structures. This paper explores how her body, marked by both physical and psychological violence, becomes a battleground for identity reconstruction. This interpretation contributes to ongoing discussions on the intersection of gender, power, and the body, offering a fresh perspective on the existential and symbolic dimensions of Kang’s novel.